Strategies of Arabicization of Information Technology Terminology in UNESCO Terminological Documents - Jamil, Muhammad; Fatoni, Ahmad Sirfi (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study analyzes the strategy of Arabization of information technology terms in UNESCO's official terminological documents to reveal the Arabic language's response to the development of modern science. This study employs a descriptive–analytical research design using standardized information technology terms extracted from UNESCO’s official terminological documents as the primary data source. The data were collected through systematic documentation and classification of terminological entries, and were analyzed qualitatively using the theoretical framework of taʿrīb and Arabic morphological analysis to identify patterns of linguistic adaptation. The results of the study show three main strategies of Arabization, namely semantic matching through internal Arabic language resources, phonetic-morphological naturalization in accordance with sharaf patterns, and pure borrowing with limited phonetic adaptation. These findings confirm that Arabization in UNESCO documents is flexible and contextual, reflecting a balance between preserving the structure of the Arabic language and the needs of global technology terminology.ners in enhancing the effectiveness of character education in primary schools.